Digital Management and its Impact on Raising the Efficiency of Employee Performance (A field study on a sample of Iraqi private companies) - Hussein, Israa Abdul Karim; Nabil, Dr. Jawad (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
The advancement of technology and communication has necessitated changes in publicadministration worldwide. Countries must adapt to these changes to demonstrate growth. It iscrucial for organizations to empower employees through new digital methods overseen by administrative authorities. This ensures effective leadership across all departments to achieve organizational goals. Research suggests evaluating the company's organizational structure for digital management suitability, aligning with its goals, and prioritizing employee skill development and continuous education.